Estimated emissions vehicles on the road - Inche Mitma, Jorge (2001)
The present article, presents a methodology for the estimate of vehicular emissions, produced by the combustion of the fuel which are liberated by the escape of the vehicle. With this end the emissions are quantified using equations that relate the vehicular activity and factors of emissions.